Observations and modelling of shoreline and multiple sandbar behaviour on a high-energy meso-tidal beach. (1st May 2018) - Splinter, Kristen D.; Gonzalez, Maria V.G.; Oltman-Shay, Joan; Rutten, Jantien; Holman, Robert
Abstract: This contribution describes 10 years of observed sandbar and shoreline cross-shore position variability at a meso-tidal, high energy, multiple sandbar beach. To examine relationships between the temporal variability in shoreline/sandbar position with offshore wave forcing, a simple equilibrium model is applied to these data. The analysis presented in this paper shows that the equilibrium model is skilled at predicting the alongshore-averaged, time-varying position of the shoreline (R = 0.82) and the outer sandbar position (R = 0.75), suggesting that these end members of the nearshore sediment system are most strongly influenced by offshore wave forcing in a predictable, equilibrium-forced manner. The middle and inner bars are hypothesized to act as sediment transport pathways between the shoreline and the outer bar. Prediction of these more transient features by an equilibrium model was less skilful. Model coefficients reveal that these two end members (outer bar and shoreline) in the sediment system act in opposite directions to changes in the annual offshore wave forcing. During high wave events, sediment is removed from the shoreline and deposited in the nearshore sediment system with simultaneous landward retreat of the shoreline and offshore migration of the outer sandbar. While both end member features have cycles at annual and inter-annual scales, their respective equilibrium response factor differs by almost a factor of 10, with the shoreline responding around an inter-annual mean (ϕ = 1000 days) and the outer bar responding around a seasonal mean (ϕ = 170 days). The model accurately predicts shoreline response to both mild (e.g. 2004/05, 2008/09) and extreme (e.g. 2005/06, 2009/10) winter storms, as well as their summer recovery. The more mobile and dynamic outer sandbar is well-modelled during typical winters. Summer onshore sandbar migration of the outer bar in 2005 and 2006 is under-predicted as the system transitioned between a triple (winter) and double (summer) sandbar system. The changing of the number of bars present in the system is something that this simple model cannot predict. Analysis of the data suggests that this multi-bar system adjusts its cross-shore seasonal movement when there is a significant change in the sediment supply to the system (e.g., nourishment projects, severe storms). Highlights: Equilibrium behavior of the offshore bar and shoreline is reproduced by a simple empirical model. The sandbar system at Benson Beach, WA displays a high degree of spatial and temporal variability. Modelling reveals that the 2 outer bars are coupled while the inner bar is coupled to the shoreline. The number of sandbars present varies with seasonal wave climate and sediment supply.